Limb segment load inhibits post activation depression of soleus H-reflex in humans - Tseng, Shih-Chiao (2012)
OBJECTIVE: We investigated the effect of various doses of limb segment load on soleus H-reflex amplitude and post activation depression in healthy individuals. We also explored the influence of limb segment load on spinal circuitry in one individual with chronic SCI. METHODS: 28 healthy adults and one SCI subject received compressive loads applied to the top of their knee at varied doses of load (10%, 25%, and 50% of the body weight). Soleus H-reflexes were measured before (baseline) and during the loading phase. RESULTS: There were no significant differences in H-reflex amplitudes during the 50 % BW load-on phase as compared to either baseline session or the load-off phase. However, the post activation depression was decreased over 9% (p < 0.05) during the load-on phase compared to the load-off phase and scaled according to load (50%>25%>10%). The post activation depression ratio also appears less responsive to varying loads after chronic SCI. CONCLUSIONS: Limb segment load decreases post-activation depression in humans. These findings suggest that the mechanism associated with post activation depression is modulated by limb segment load, and may be influenced by spinal reorganization after SCI. SIGNIFICANCE: Future studies will determine if various levels of spasticity modulate the response of limb segment load on post activation depression in those with acute and chronic SCI.